Leptin regulation of neuronal morphology and hippocampal synaptic function - Harvey, Jenni (Frontiers in Synaptic Neuroscience, 2013)
The central actions of the hormone leptin in regulating energy homeostasis via the hypothalamus are well documented. However, evidence is growing that this hormone can also modify the structure and function of synapses throughout the CNS. The hippocampus is a region of the forebrain that plays a crucial role in associative learning and memory and is an area also highly vulnerable to neurodegenerative processes. Recent studies indicate that leptin is a potential cognitive enhancer as it modulates the cellular processes underlying hippocampal-dependent learning and memory including dendritic morphology, glutamate receptor trafficking and activity-dependent synaptic plasticity. Here, we review the recent evidence implicating the hormone leptin as a key regulator of hippocampal synaptic function and discuss the role of leptin receptor-driven lipid signaling pathways involved in this process.